UPAYA PENGEMBANGAN VARIETAS JAGUNG TAHAN KERING MELALUI EVALUASI GALUR SMCT-2 - Wayan Sudarka; Sang Made Sarwadana; I Gusti Ngurah Raka; Ni Luh Made Pradnyawati; I Gusti Alit Gunadi (Environmental Research Center (PPLH) of Udayana University, 2009)
The research entitled “ Developping drought resistance of corn variety via evaluation of SMCT-2 line ” which aimed to achieve of agronomic characteristic varians and yield potential of SMCT-2 compare with SMCT-1 line and their parent. This research considered to conduct at dry season in Denpasar about 2007 and 2008. Selection method on this research is purporsive random sampling. Evaluation of variance selection line (SMCT-2) compare to parent showed significant different (F= 0,05) of some variables such as total of leafs, plants hight, leafs area, internodes, diameter of stems, position of ears corn, silks period, grains line on ears, ears length, grains weight per plant, weight of 100 grains per plant. Non-significant variance of variables is: length of internode, ears corn diameter, dry weight of raw materials, total of productive ears corn, initial period of tassels. Variances of entire variables of SMCT-2 relatively are lower than parent and SMCT-1 line. The higher variances of SMCT-2 are showed on height of plants (526,30) , leafs area (4011,10), position of ears-corn (205,58), dry weight of raw materials (5641,37), dry weight of ears-corn per plant (188,82), total of grains per plant (4335,26), dry weight of grains per plant (276,58). Coerffient of variance showed that SMCT-2 line, SMCT-1 line and parent less than 20 %. Average of variables to support production SMCT-2 line yields are relatively higher than parent is showed by: length of ears corn (13,20 %), dry weight of ears corn (5,6 %), total of grains per ear-corn (15,23 %), lines number of seeds per ear corn (4,80 %), dry weight of grains per plant (27,61 %), dry weight 100 grains per plant (3,33 %). Dry weight of yield SMCT-2 line was founded 5,02 ton per hectar, which is higher 4,58 % than SMCT-1 (4,8 ton per hectare), and is higher 8,71 % than parent (3,9 ton per hectare), with population 50.000 plants per hectare. This line was relative resistance on drought, show that was devolved to produced new variety for the arids areas.